Atopia em Pierre Hadot (parte 1) - de Almeida Júnior, George Matias (Revista Archai, 2016)
We will present some aspects of Pierre Hadot´s conception of ancient philosophy understood as “way of life” and practised through the so called “spiritual exercises”, the author´s main thesis in the works which we propose to evaluate. From this perspective, we firstly emphasize the relevance of the figure of Socrates in the constitution of Hadot´s point of view and, above all, how the author mobilises the notion of atopia, which can be broadly understood as the philosopher´s strangeness (etrangete) in the human world, derived from the figure of Socrates in Plato´s dialogues. Secondly, we present the meanings of this strangeness, pointing out its origins, some of its conceptual possibilities as well as some of the aporiai which lie in Hadot’s thesis. We also believe that Hadot´s reflection, besides bringing out the question of atopia, seems to be atopic itself in a sense that it will be pointed out. Keywords: atopia; Socrates; Pierre Hadot; personality; ways of life.